Effects of Seasonal Variations on Sandy Beach Groundwater Table and Swash Zone Sediment Transport - Norasman, Othman; Ahmad Khairi, Abd Wahab; Mohamad Hidayat, Jamal (Coastal Engineering Research, 2014)
The hydrodynamics in the swash zone significantly affected the sediment transport mechanisms that mostly control beach face morphology especially under different weather conditions. Rainfall distribution patterns during dry and wet seasons in Peninsular Malaysia will influence groundwater table elevation and the beach profile. This study is aimed at investigating the effects of seasonal variations to beach groundwater elevations and surface profile changes. This work was undertaken at the Desaru Beach, Johor. Rainfall depth, groundwater table, tides, beach profiles, swash depth and swash velocity data were monitored and investigated at the study area. The results showed that the groundwater table was affected by rainfall patterns; higher during the wet season and lower during the dry season. The beach profile also showed erosive condition due to increasing of offshore sediment transport during the wet season, whereas in the dry season the beach profile showed accretion condition due to the increasing of onshore sediment transport. Swash properties like swash water depth and velocity were also monitored and analysed during this study in order to get a clear view about the saturation level effect due to seasonal variations into a infiltration processes at the swash zone. Finally the data showed that there is a lag time between rising and falling of groundwater tables and tides due to the lower hydraulic conductivity effect.